Evaluation of sun-dried Opuntia ficus-indica var. Algerian cladodes in sheep diets - Zeeman, Desiree Carla (University of the Free State, 2005)
The effect of incremental inclusion levels (0, 12, 24 and 36%) of dried and coarsely ground Opuntia cladode material in balanced diets to substitute some of the luceme was investigated with regard to the digestibility of the diets, as well as the effects of the Opuntia cladodes on rumen variables (pH, ammonia levels and volatile fatty acid concentration). The digestibility trial was conducted over a period of 19 days with 24 young Dorper wethers; divided in four treatment groups (TO, Tl2, T24 and T36) each receiving a different inclusion level of Opuntia cladodes. Feed grade urea was included in diets containing Opuntia cladodes to compensate for the lower crude protein (CP) content of the Opuntia cladodes. Water consumption, food intake and digestibility of the diets were measured. The inclusion of incremental levels of Opuntia cladodes caused a decrease in organic matter (OM), acid-detergent fibre (ADF), neutral-detergent fibre (NDF) and gross energy (GE), while the ether extract (EE) content increased. The water intake of the wethers increased significantly (P<0.05) with the increased Opuntia cladode content of the diets while urine excretion remained the same. The level of food intake as well as the faeces dry matter (DM) excreted remained the same for all diets but the DM content of the faeces decreased with the higher Opuntia cladode inclusion levels. This is ascribed to the mucilage content of the Opuntia cladodes. The incremental inclusion levels of Opuntia cladodes caused an increase in apparent DM digestibility coefficient (from 0.673 for diet TO to 0. 716 for diet T36) suggesting that the Opuntia cladodes are highly digestible. Due to the low OM content of the Opuntia cladodes there was a decrease in the digestible energy (DE) content from diet TO (17.253 MJ/kg) to diet T36 (12.689 MJ/kg). In spite of these results there appeared to be no discemable difference in overall performance of the sheep on the various diets. The rumen fermentation was studied with 4 rumen cannulated Dorper wethers in a trial with a crossover design during four successive 14-day periods. The incremental inclusion levels of Opuntia cladodes in the diets had no significant (P<0.05) influence on the rumen ammonia (NH3) concentration. The rumen NH3 concentration was consistently between 9.4 mg NH3/IOO ml rumen fluid and 58.5 mg NH3/lOO ml rumen fluid, with a peak at 2 hours postfeeding. The inclusion of Opuntia cladodes in the diets also had no effect on the rumen pH. The rumen pH consistently ranged between 6.3 and 7.2. The inclusion level of Opuntia cladodes also had no significant (P<0.05) effect on the rumen volatile fatty acids (VF A) concentration or the proportions of the acetate, propionate or butyrate in the total VF A pool in the rumen. There was also now significant (P<0.05) difference in the in sacco DM disappearance in the rumen, again suggesting no effect on the microbial activity in the rumen. The use of dried and coarsely ground Opuntia cladodes in balanced diets for sheep as partial substitution for coarsely ground luceme hay to an inclusion level of 36% in the diet is, therefore, a viable option and can decrease the cost of sheep diets. In practical terms the greatest challenge to overcome will be the successful drying of large quantities of Opuntia cladodes, thus enabling farmers to transport it over longer distances from the production areas to where it can be used as livestock feed. This study offer some suggestions about cutting and drying of the Opuntia cladodes but further research is required to determine what possible influence the processing and drying of the cladodes in the sun may possibly has on its nutritional value. More research is required on the role and especially the effects of mucilage on the digestive processes in ruminant feeds.

Die invloed van inkrementele insluitingspeile (0, 12, 24 en 36%) gedroogde en grof gemaalde Opuntia kladode materiaal in gebalanseerde diete ter gedeeltelike vervanging van lusem is ondersoek ten opsigte van die verteerbaarheid van die vier diete, asook die invloed van die Opuntia kladodes op rumen veranderlikes (pH, ammoniak- en vlugtige vetsuurkonsentrasies). 'n Verteringsproef is oor 'n periode van 19 dae met 24 jong Dorperhamels uitgevoer wat in vier behandelingsgroepe (TO, T12, T24 en T36) verdeel is en diete met verskillende insluitingspeile van Opuntia kladodes ontvang het. Voergraad ureum is in die diete wat Opuntia kladodes bevat het ingesluit om te kompenseer vir die laer ruproteYeninhoud (RP) van die Opuntia kladodes. Die water- en voerinname deur die hamels en die verteerbaarheid van die vier diete is bepaal. Die insluiting van inkrementele peile van Opuntia kladodes het 'n afname in organiese materiaal (OM), suurbestande vesel (ADF), neutraalbestande vesel (NDF) en bruto energie (BE) tot gevolg gehad, terwyl die eterekstrakinhoud verhoog het. Die waterinname van die hamels het betekenisvol (P<0.05) gestyg met toenemende Opuntia kladode insluiting in die diete, terwyl urine uitskeiding onveranderd gebly het. Die voerinname sowel as die droe materiaal (DM) van die misuitskeiding het dieselfde gebly vir die diete, maar die DM-inhoud van die mis was laer met toenemende Opuntia kladode insluitingspeile. Dit word toegeskryf aan die hoe slymgominhoud ("mucilage") van die Opuntia kladodes. Die inkrementele insluitingspeile van Opuntia kladodes het 'n toename in die skynbare DM verteerbaarheid koeffisient (vanaf 0.673 vir dieet TO tot 0.716 vir dieet T36) tot gevolg gehad; <lit dui daarop dat Opuntia kladodes hoogs verteerbaar is. As gevolg van die laer OM-inhoud van die Opuntia kladodes was daar 'n afname in die verteerbare energie (VE) vanaf dieet TO (17.253 MJ/kg) na dieet T36 (12.689 MJ/kg). Ten spyte van die resultate was daar geen merkbare verskil in diereprestasie van die hamels op die verskillende diete nie. Die rumenfermentasie is bestudeer met vier rumengefistuleerde Dorperhamels gedurende vieropeenvolgende periodes van 14 dae in 'n proef met 'n omslagontwerp. Die inkrementele insluitingspeile van Opuntia kladodes in die diete het nie 'n betekenisvolle (P<0.05) invloed op die rumen ammoniak (NH3) konsentrasies gehad nie. Die rumen NH3 konsentrasies was deurgaans tussen 9.4 mg NH3/lOO ml rumenvloeistof en 58.5 mg NH3/lOO ml rumenvloeistof, met 'n piek 2 uur na voeding. Die insluiting van Opuntia kladodes het ook geen betekenisvolle (P<0.05) invloed op rumen pH gehad nie; die rumen pH was deurgaans tussen 6.3 en 7.2. Die insluitingspeile van Opuntia kladodes het geen betekenisvolle (P<0.05) invloed op die konsentrasie van die rumen vlugtige vetsure (VVS) of die verhouding van asyn-, propion- of bottersuur in die totale VVS poel in die rumen gehad nie. Daar was ook geen betekenisvolle (P<0.05) verskil in in sacco DM verdwyning in die rumen nie, wat weer eens daarop dui dat geen invloed op die mikrobiese aktiwiteit in die rumen uitgeoefen is nie. Die aanwending van gedroogde en grof gemaalde Opuntia kladodes in gebalanseerde diete vir skape ter gedeeltelike vervanging van grof gemaalde lusernhooi tot 'n insluitingspeil van 36% in die dieet is, derhalwe, 'n haalbare opsie en kan die koste van skaapdiete verminder. In praktiese terme is die belangrikste uitdaging wat oorbrug moet word die suksesvolle droging van groot hoeveelhede Opuntia kladodes om boere sodoende in staat te stel om <lit oor !anger afstande te vervoer na gebiede waar <lit as veevoer benut kan word. Hierdie studie hied voorstelle oor wyses om Opuntia kladodes te sny en te droog, maar meernavorsing is nodig om te bepaal wat die moontlike invloed van prosessering en droging van die kladodes in die son op die voedingswaarde mag he. Meer navorsing is ook nodig oor die rol en veral die invloed van slymgom op die verteringsprosesse by herkouer diete.
Dissertation (M.Sc.Agric. (Animal, Wildlife and Grassland Sciences))--University of the Free State, 2005
Keywords: Opuntia ficus-indica; Sheep -- Feed utilization efficiency; Sheep -- Feeding and feeds